2016
DOI: 10.1037/neu0000315
|View full text |Cite|
|
Sign up to set email alerts
|

The effectiveness and unique contribution of neuropsychological tests and the δ latent phenotype in the differential diagnosis of dementia in the uniform data set.

Abstract: Objective Two main approaches to the interpretation of cognitive test performance have been utilized for the characterization of disease: evaluating shared variance across tests, as with measures of severity, and evaluating the unique variance across tests, as with pattern and error analysis. Both methods provide necessary information, but the unique contributions of each are rarely considered. This study compares the two approaches on their ability to differentially diagnose with accuracy, while controlling f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 82 publications
(113 reference statements)
0
31
0
Order By: Relevance
“…Etiology‐specific cognitive variance is residual (i.e., orthogonal) to δ [20]. This suggests that attempts to define disease‐specific biomarker panels relating to etiology‐specific variance in cognitive performance will not be associated with dementia severity.…”
Section: Discussionmentioning
confidence: 99%
“…Etiology‐specific cognitive variance is residual (i.e., orthogonal) to δ [20]. This suggests that attempts to define disease‐specific biomarker panels relating to etiology‐specific variance in cognitive performance will not be associated with dementia severity.…”
Section: Discussionmentioning
confidence: 99%
“…John et al. [25] demonstrated that δ scores are unable to distinguish between any combination of dementing conditions. Instead, only “unique” (i.e., “domain‐specific”) variance, residual to δ, was able to make such discriminations.…”
Section: Discussionmentioning
confidence: 99%
“…Second, John et al. 's [25] finding suggests that the cognitive differences that distinguish dementing illnesses may be orthogonal to δ and therefore unrelated to dementia severity. This includes domain‐specific variance, by definition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…δ is highly accurate in distinguishing demented cases (16), but it is entirely “agnostic” as to dementia’s etiology (17). If p can be shown to be associated specifically with δ then it would directly implicate dementia itself as the transdiagnostic determinant of global psychopathology, link p to intelligence, and constrain p ’s biology to that of g and δ.…”
Section: Introductionmentioning
confidence: 99%